Lifetime experience of multiple common mental disorders and 19-year mortality: results from a Canadian population-based cohort. (2020) - Kingsbury, M.; Sucha, E.; Horton, N. J.; Sampasa-Kanyinga, H.; Murphy, J. M.; Gilman, S. E.; Colman, I.
Abstract: Aims: To examine the impact of multiple psychiatric disorders over the lifetime on risk of mortality in the general population. Methods: Data came from a random community-based sample of 1397 adults in Atlantic Canada, recruited in 1992. Major depression, dysthymia, panic disorder, generalised anxiety disorder and alcohol use disorders were assessed using the Diagnostic Interview Schedule (DIS). Vital status of participants through 2011 was determined using probabilistic linkages to the Canadian Mortality Database. Cox proportional hazard models with age at study entry as the time scale were used to investigate the relationship between DIS diagnoses and mortality, adjusted for participant education, smoking and obesity at baseline. Results: Results suggested that mood and anxiety disorders rarely presented in isolation – the majority of participants experienced multiple psychiatric disorders over the lifetime. Elevated risk of death was found among men with both major depression and dysthymia (HR 2.56; 95% CI 1.12–5.89), depression and alcohol use disorders (HR 2.45; 95% CI 1.18–5.10) and among men and women who experienced both panic disorder and alcohol use disorders (HR 3.80; 95% CI 1.19–12.16). Conclusion: The experience of multiple mental disorders over the lifetime is extremely common, and associated with increased risk of mortality, most notably among men. Clinicians should be aware of the importance of considering contemporaneous symptoms of multiple psychiatric conditions.